2010
DOI: 10.1097/fpc.0b013e328338073a
|View full text |Cite
|
Sign up to set email alerts
|

A nonsynonymous variation in MRP2/ABCC2 is associated with neurological adverse drug reactions of carbamazepine in patients with epilepsy

Abstract: These results strongly suggest that the A-allele of the MRP2 single nucleotide polymorphism c.1247G>A is associated with adverse neurological drug reactions to carbamazepine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 36 publications
1
59
2
1
Order By: Relevance
“…It is noteworthy that the SNP 21214GϾA (V417I; rs2273697; 16 heterozygotes, 2 homozygotes), which has not been reported to affect MRP2 expression, showed a significantly (P Ͻ 0.004) higher expression of MRP2 (1.87 Ϯ 0.77 fmol/g membrane protein; n ϭ 18) versus the wild-type livers (1.34 Ϯ 0.38 fmol/g membrane protein; n ϭ 27). This SNP has been associated with greater central nervous system adverse effects (but not efficacy) of carbamazepine, presumably because of lower MRP2 activity (Kim et al, 2010). It is possible that this SNP increases the expression of MRP2 while reducing its activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the SNP 21214GϾA (V417I; rs2273697; 16 heterozygotes, 2 homozygotes), which has not been reported to affect MRP2 expression, showed a significantly (P Ͻ 0.004) higher expression of MRP2 (1.87 Ϯ 0.77 fmol/g membrane protein; n ϭ 18) versus the wild-type livers (1.34 Ϯ 0.38 fmol/g membrane protein; n ϭ 27). This SNP has been associated with greater central nervous system adverse effects (but not efficacy) of carbamazepine, presumably because of lower MRP2 activity (Kim et al, 2010). It is possible that this SNP increases the expression of MRP2 while reducing its activity.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo studies have suggested that CBZ or its active metabolite is a substrate of ABCC2 and can interfere with drug efficacy by effluxing it out (6,16). ABCC2 has been demonstrated to be involved in CBZ efficacy in the ABCC2-deficient rat model (6).…”
Section: Introductionmentioning
confidence: 98%
“…Genotypes of OATP1B1 are associated with interindividual differences in the systemic exposure of statins (Nishizato et al, 2003;Chung et al, 2005;Lee et al, 2005;Pasanen et al, 2006Pasanen et al, , 2007. Another report has described the association of single nucleotide polymorphisms of MRP2 with the plasma levels of its substrates, phase II metabolites of isoflavonoids (Kato et al, 2012), or adverse reactions to drugs (Kim et al, 2010). [ 11 C]DPV will provide quantitative information on the effect of single nucleotide polymorphisms on OATP1B1 and MRP2 activities.…”
mentioning
confidence: 99%